Managing for Innovation. - Glass, Robert L. (Communications of the ACM, 2008)
The article discusses the views of software engineer Watts Humphrey regarding the role of people and processes in software innovations. In his book "Managing for Innovation: Leading Technical People," Humphrey focused on the role of creativity and work to produce innovations. Humphrey suggested that technical personnel were better at producing innovations when given more freedom by managers, but that managers with technical skills could improve innovation development. He commented that personnel should focus on how the application will be used and discussed the role of age in creativity.